Força muscular e marcha de idosos: resultados de um programa de exercício físico multimodal - PONTES, Helen Tatiane Santos (2022)
Changes in the age structure of the national population make the age pyramid characteristic of an aging population. There is a need to develop prevention and rehabilitation strategies aimed at improving the quality of life of this increasingly comprehensive population. Current research gives evidence that, compared to simple stimulation protocols, dual-task multimodal exercise interventions may be more efficient, improving on several physical variables, but there are still few studies using multimodal stimulation protocols. The present study aimed to investigate the effect of an intervention program composed of dual task multimodal exercises on muscle strength and gait speed in healthy elderly. The intervention group was composed of 41 elderly (67.96 ± 6.74 years old) and the control group by 35 elderly (67.76 ± 5.54 years old) who assessed muscle strength and gait speed in Single and double task. Twentyfour multimodal training sessions were performed consisting of warm-up, aerobic exercise, resistance exercise and stretching twice a week with 75 minutes each. After the sessions, the intervention group had a significant increase in lower limb muscle strength (p <0.001) as well as an increase in gait velocity in a simple task (p = 0.010), but not for MMSS muscle strength or gait velocity. double task (p> 0.05). Therefore, improving the functionality required in the daily life activities of the elderly.